MENINGKATKAN KUALITAS PEMASARAN UMKM MELALUI INOVASI SOSIAL MEDIA MARKETING PADA PELAKU USAHA KERIPIK DI DESA DOMAS - Agus Miftakus Surur; Puspita Dyah Paramita (Institut Agama Islam Negeri Kerinci, 2022)
Purpose: To get an idea of ​​how MSMEs cassava and banana chips in Domas Village can take advantage of other social media by providing innovations to the products sold and expanding marketing using Instagram, Twitter, for business benefits and introducing these products to the wider community in order to gain potential share. wider market. Design/methodology/approach: This study is a qualitative research that aims to identify the role of social media in increasing the marketing activities of cassava and banana chips business owners in Temboro Hamlet, Domas Village. The method of data collection was done by interview and observation techniques. Findings: MSME actors have not utilized social media marketing optimally for their business interests. Research implications: With the results of this study, it is hoped that MSME actors can increase marketing and sales by reaching a broad market share